The effect of argument-driven inquiry to pre-service biology teachers’ argumentation skills and metacognitive awareness in Mendelian genetics - Rizqa Devi Anazifa; P. Paidi; Anggi Tias Pratama; Atik Kurniawati (University of Muhammadiyah Malang, 2024)
In recent years, pre-service teacher education programs have recognized the importance of equipping future educators with the necessary skills such as argumentation skills and metacognitive awareness. However, the extent to these skills in ore-service biology teachers remains relatively unexplored. This study aimed to explore the effect of argument-driven inquiry on pre-service biology teachers’ argumentation skills and metacognitive awareness. This study also investigated the correlation between argumentation skills and metacognitive awareness in pre-service biology teachers. This research was conducted as quasi experiment using nonrandomized control group pretest–post-test design with two classes. One class as experiment group (N=44) which participated in series of activities in laboratory work using argument-driven inquiry, and control group (N=44) which participated in the regular laboratory activities. The laboratory work focused on the topic of mendelian genetic. This research was conducted on the second year of pre-service biology teachers in the Department of Biology Education. Data were generated by administrating pre-test and post-test on argumentation skill using open-ended question and metacognitive awareness using Metacognitive Awareness Inventory (MAI). Result showed a significant difference between experimental group and control group in argumentation skills (p value= .016) as well as in metacognitive awareness (p value = .005). However, the correlation between argumentation skills and metacognitive awareness were relatively low (r= -.119). This research findings can be used as suggestions for policy makers and educational institute to integrate argumentation skills and metacognitive awareness in designed for professional development program in teacher training program.